The handbook of the psychology of communication technology - Sundar, S. Shyam (Chichester, West Sussex, UK ; Malden, MA : John Wiley & Sons, Inc., 2015)
The Handbook of the Psychology of Communication Technologyoffers an unparalleled source for seminal and cutting-edge researchon the psychological aspects of communicating with and via emergentmedia technologies, with leading scholars providing insights thatadvance our knowledge on human-technology interactions. A uniquely focused review of extensive research ontechnology and digital media from a psychological perspective Authoritative chapters by leading scholars studyingpsychological aspects of communication technologies Covers all forms of media from Smartphones toRobotics, from Social Medi.
Future WorkConclusions; Acknowledgments; References; Chapter 8 Psychological Aspects of Technology Interacting with Humans; Virtual Characters; Interactive PEFiC; I-PEFiC and Affective Decision Making; Silicon Coppélia; Realism? Epistemics of the Virtual; Ethics: Moral Reasoner; Affordances: Creative Machines; Caredroids: Humanoids Taking Care; Conclusions; Acknowledgments; Notes; References; Part III Technological Affordances and Social Interaction; Chapter 9 Social Network Site Affordances and Their Relationship to Social Capital Processes; Overview of Social Media; Social Network Sites
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Communication and technology -- Psychological aspects; Information technology -- Psychological aspects; Communication -- Psychological aspects; SOCIAL SCIENCE / General; Communication -- Psychological aspects; Communication and technology -- Psychological aspects; Information technology -- Psychological aspects; Electronic books; Electronic books